MODERNISASI PEMBUNUHAN ANAK - Muhammad Yogi Galih Permana; Muhamad Arifin (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2022)
This study aims to reveal the continuity and development of one of the deviant human behaviors to their own offspring, that is killing their children. This study examines historical data as well as the role of various technological and scientific advances on child homicide. By analyzing historical data that has been summarized from various references, the researchers try to find similarities and differences between the practice of child homicide in the past and the practice of child homicide in the modern era. At the same time, researchers are also trying to find the influence of modern technology on some child homicide attempts. The results of this study indicate that the motive for child homicide still revolves around two things; gender discrimination and economic concerns. These two things are the most common reasons behind the practice of child homicide. And in the modern era, there is another reason why child homicides are increasing, namely unwed pregnancy, especially in women at an early age, as a result of the rampant promiscuity in society.